EDUKASI DIGITALISASI PEMASARAN DAN PENCATATAN KEUANGAN PENGRAJIN KERIPIK KARANGBOLO UNGARAN BARAT - Srimindarti, Ceacilia; Hardiningsih, Pancawati; Anggana Lisiantara, Greg; Ardinata, Muhamad; Sulastri, Sulastri (Jurnal Abdimas Musi Charitas, 2023)
Karangbolo Village, as a center for processed chip products and diversification, has been able to compete and sustain the production of regional superior products. The increased market demand has led to a rise in production. The Covid-19 pandemic situation has posed challenges for chip artisans, particularly in terms of a lack of understanding of digitalization technology for marketing and the discontinuity of financial records, making it difficult to determine turnover accurately. This activity is related to the opportunity to increase income sustainably, but it requires support in both knowledge and skill. Skills education is provided to chip artisans in Karangbolo Village. Training results indicate that artisans can optimize digital marketing and simple financial recording based on Excel. Artisans are capable of updating products through WordPress. Furthermore, they can improve product packaging with various variants and sizes to enhance attractiveness and market value.